Prestigious stock exchanges: A network analysis of international financial centers - Nicola Cetorelli; Stavros Peristiani (Federal Reserve Bank of New York, 2009)
In this paper, we use methods from social network analysis to assess the relative importance of financial centers around the world. Using data from virtually the entire universe of global equity activity, we present two sets of complete rankings for up to forty-five separate locations for the 1990-2006 period. The first phase of our analysis evaluates international stock exchanges based on their ability to attract global initial public offerings (IPOs). The second phase compares the capacity of these exchanges to provide an efficient trading platform for cross-listed companies. U.S. exchanges are effectively the unique hosts for cross-border equity activity originating from many other locations. Moreover, they are the destination of choice for most companies coming from locations with highly prestigious exchanges. We find that, despite a diminished ability to attract cross-border IPOs, U.S. exchanges have maintained an undisputable lead in global equity activity throughout the entire sample period. We do find evidence of the rising importance of competing exchanges - in particular, the London Stock Exchange, the Deutsche Börse, and the Hong Kong Stock Exchange - and also of an expanding role for a number of emerging market stock exchanges. However, this rising pattern reflects improved competitive conditions in a growing global market rather than a sudden decline in the activity of U.S. exchanges.
Keywords: G15; F39; G19; 330; Network analysis; stock exchanges; global equity activity